The Effect of Size, Profitability, Risk, Complexity, and Independent Audit Committee on Audit Fee (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2018)
Research on audit fees is important because it relates to professional services provided by public accountants. Whereas the transparency of information about audit fees in the company’s financial statements in Indonesia openly and apart from other service fees has only been done in the last few years, so there has not been much research related to this. Therefore, this study aims to examine the effect of size, profitability, company risk, company complexity, and independent audit committee on audit fees. A sample of 136 manufacturing companies listed on the Indonesia Stock Exchange in 2014-2016. Multiple regression analysis is used to test the hypothesis. The results of this study indicate that the size of the company, profitability, complexity of the company has a positive effect on audit fees. Company risk and an independent audit committee have no effect on audit fees.